The reduction in glutamate release is predictive of cognitive and emotional alterations that are corrected by the positive modulator of AMPA receptors S 47445 in perinatal stressed rats. (June 2018) - Morley-Fletcher, S.; Zuena, A.R.; Mairesse, J.; Gatta, E.; Van Camp, G.; Bouwalerh, H.; Riozzi, B.; Battaglia, G.; Pittaluga, A.; Olivero, G.; Mocaer, E.; Bretin, S.; et al.
Abstract: S 47445 is a positive modulator of glutamate AMPA-type receptors, possessing neurotrophic and enhancing synaptic plasticity effects as well as pro-cognitive and anti-stress properties. Here, the drug was assessed in the perinatal stress (PRS) rat model, known to have a high predictive validity with monoaminergic antidepressants. The effects of a chronic treatment (i.p.) with S 47445 were investigated on risk-taking, motivational and cognitive behavior. S 47445 (1 and 10 mg/kg) increased the exploration of the elevated-plus maze and light/dark box as well as the time spent grooming in the splash test, and improved social memory in PRS rats. Also, the effects of S 47445 were examined on the synaptic neurotransmission. The reduced depolarization-evoked glutamate release induced by PRS was corrected with S 47445 (10 mg/kg). Remarkably, the reduction in glutamate release induced by PRS and corrected by S 47445 chronic treatment was correlated with all the behavioral changes. S 47445 at 10 mg/kg also normalized the lower levels of synaptic vesicle-associated proteins in ventral hippocampus in PRS rats. Finally, S 47445 reversed the decrease of mGlu5 receptors, GR and OXTR induced by PRS. Collectively, in an animal model of stress-related disorders, S 47445 corrected the imbalance between excitatory and inhibitory neurotransmission by regulating glutamate-evoked release that is predictive of PRS behavioral alterations, and also normalized the reduction of trafficking of synaptic vesicles induced by PRS. These results support the interest of glutamatergic-based therapeutic strategies to alleviate stress-related disorders. Highlights: Need to search for new antidepressants. Glutamate neurotransmission plays a new key role in psychopharmacology. PRS rats present dysfunctions in glutamate neurotransmission and related behaviors. S 47445 AMPAR potentiator corrects PRS induced behavioral/neurochemical alterations. Valid animal models should always be included in preclinical studies.